Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Model Dicovery Learning Terintegrasi Peduli Lingkungan pada Pelajaran IPA SD Kelas V - Noliana Sartika; Endang Widi Winarni; Irwan Koto (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This research is a research on the development. This study aims to produce student worksheets (LKPD) based on the discovery learning model in integrated science learning for fifth grade elementary school to care for the environment and to foster an attitude of caring for the environment in students. The research subjects were a teacher and 19 fifth grade students at SDN 48 Lubuklinggau, South Sumatra. The data collection instrument used was an expert validation questionnaire to test the feasibility. There were 6 experts who became validators, 2 each for the material aspect, language aspect, and display aspect. For student responses, a questionnaire was used which was responded to by 19 fifth grade students and for the teacher's response, a structured interview guide was used. The results of data analysis can be concluded that the LKPD based on the discovery learning model in science learning for class V SD integrated environmental care is declared suitable for use with details of material aspects 0.72 (feasible), language aspects 0.83 (very feasible), and display aspects 0.80 (very worthy). While the results of the field test from the responses of teachers and students have met the criteria for use.